Voices of Franciszek Małkot: A Significant Exposure in the Literature of the Grand Duchy of Lithuania - Patiejūnienė, Eglė (Senoji Lietuvos literatūra, 2014)
The paper deals with a joint Lithuanian-Polish academic project aimed at the preparation of a critical publication of a little-known literary source. The source is the collection of versified texts written in Polish Tureckich y inflantskich woien [...] głos (The Voice of the Wars against the Turks and in Livonia) published in Vilnius and dedicated to the memory of the Grand Hetman of the Grand Duchy of Lithuania Jan Karol Chodkiewicz, who led the joint Polish-Lithuanian-Kazak forces in the Battle of Khotyn in 1621 and died during that battle. Among the multitude of funeral literary works that marked the death of the popular military leader, Głos (The Voice) is distinguished not only by its higher artistic value and pronounced ‘pro-Lithuanian’ orientation, but also because in the 17th century it was reprinted twice, which means it was published three times – in 1622, 1624, and in 1640. Alongside the dedication, the collection of the final edition contains five works of different size and poetic form, which are all called “Voices” of various personifications (Wars, the heraldic Gryphon, Beauty, Glory). In the first edition, next to the titles of works there was information regarding the tunes these works should be sung to, while the second edition (of which, unfortunately, only a bibliographical description has survived) included the music. A 17th-century occasional publication of secular content with the music is an immense rarity even in the context of the whole Republic of Two Nations, and a unique phenomenon in the Grand Duchy of Lithuania.The author of the paper presents the analysis of all works of the collection which was carried out by the Polish scholar and project coordinator Dariusz Chemperek. To it, she has added critical observations and the material she collected herself. It becomes clear that the analysed collection is extremely significant in the literary and cultural context of 17th-century Lithuania. It is an obvious proof that as early as the first half of the 17th century there existed the genre of the original song, which means that Tureckich y inflantskich woien [...] głos provides valuable new material on the history of Lithuanian musical culture. The individual texts of the collection represent literary genres which were not yet linked with Lithuania and do not appear in the history of Lithuanian literature, in particular, duma and pieśń nowiniarska, or the song of the news.
Keywords: -